Science and Ethics / La Science et l'Éthique - Demers, Patricia, 1946-; Alper, Howard (Book collections on Project MUSE., 2001)
The papers from the 2000 symposium of the Royal Society of Canada explore the crucial relationship between science and ethics. In the six papers, presented by scholars and practitioners in fields as varied as psychiatry, law, philosophy, and ethics, the contributors address the central place of ethics in scientific policy, research, and practice. Historic decisions like the place of the 1947 Nuremberg Code, adopted by the International War Crimes Tribunal to establish the foundational ethical principals of research involving human subjects; contemporary policy concerning, and institutional responsibility for, the protection of human subjects; science, technology, and copyright laws in Canada; xenotransplantation (the process of grafting living cells, tissues, and organs from animals to human beings);the privatization of biomedical research; and the relationship between ethics, policies, and research experts: these are the topics under discussion in this timely collection of papers.